2006
DOI: 10.3892/ijo.28.6.1409
|View full text |Cite
|
Sign up to set email alerts
|

LAGλ-1: A clinically relevant drug resistant human multiple myeloma tumor murine model that enables rapid evaluation of treatments for multiple myeloma

Abstract: Abstract. We set out to generate new human myeloma tumors that grow in immunodeficient mice and can be used for pathophysiological studies and rapid evaluation of new therapies. Fresh whole core bone marrow (BM) biopsies taken from 33 myeloma patients were engrafted into the hind limb muscle of severe combined immunodeficient (SCID) mice. Human Ig was detected in 28/33 mice and three grew palpable tumors displaying many features of human myeloma including morphology, immunophenotype and BM plasmacytosis. Follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(38 citation statements)
references
References 17 publications
1
37
0
Order By: Relevance
“…In our preclinical in vivo studies using our severe combined immunodeficiency --hu myeloma models, we showed that administration of low-dose PLD administered on a daily basis produced more marked anti-myeloma effects and was better tolerated compared to administering PLD at a higher dose once weekly. 32 Clinical data has shown that increasing the length of each cycle while reducing the dose of bortezomib and the dose and schedule of PLD can result in similar efficacy and improved tolerability for relapsed/refractory (R/R) 13 and untreated 33 MM patients receiving these two agents with intravenously administered dexamethasone. In both of these studies, the traditional dosing of bortezomib at 1.3 mg/m 2 and oral dexamethasone 40 mg both on days 1, 4, 8 and 11 with PLD at 30 mg/m 2 on day 4 on a 3-week cycle 12,15 was modified to a longer 4-week cycle in which PLD at 5 mg/m 2 , bortezomib at a lower dose (1 mg/m 2 ) and dexamethasone administered intravenously (IV) at 40 mg were all given on days 1, 4, 8 and 11.…”
Section: Introductionmentioning
confidence: 99%
“…In our preclinical in vivo studies using our severe combined immunodeficiency --hu myeloma models, we showed that administration of low-dose PLD administered on a daily basis produced more marked anti-myeloma effects and was better tolerated compared to administering PLD at a higher dose once weekly. 32 Clinical data has shown that increasing the length of each cycle while reducing the dose of bortezomib and the dose and schedule of PLD can result in similar efficacy and improved tolerability for relapsed/refractory (R/R) 13 and untreated 33 MM patients receiving these two agents with intravenously administered dexamethasone. In both of these studies, the traditional dosing of bortezomib at 1.3 mg/m 2 and oral dexamethasone 40 mg both on days 1, 4, 8 and 11 with PLD at 30 mg/m 2 on day 4 on a 3-week cycle 12,15 was modified to a longer 4-week cycle in which PLD at 5 mg/m 2 , bortezomib at a lower dose (1 mg/m 2 ) and dexamethasone administered intravenously (IV) at 40 mg were all given on days 1, 4, 8 and 11.…”
Section: Introductionmentioning
confidence: 99%
“…THP-1 cells that express GFP (THP-1/GFP) were mixed with human MM LAG-1 40 cells that express PTN 21 and were injected into C.B-17 SCID mice. The animals were killed at 6 weeks and the tumors were analyzed by fluorescence microscopy and scanned using confocal microscopy.…”
Section: Following Coinjection With MM Cells Thp-1 Cells Express Vecmentioning
confidence: 99%
“…40 The LAG-1 tumor was established from serial intramuscular passages of BM derived from an IgG-producing MM patient and has been maintained for more than 5 years. 40 Animal studies were conducted according to protocols approved by the Animal Research Committee at the Institute for Myeloma & Bone Cancer Research. We injected subcutaneously 10 6 LAG-1 cells, 10 6 THP-1 monocytes, or coinjected both cell types into SCID mice.…”
Section: In Vivo Studiesmentioning
confidence: 99%
“…This led to a high response rate but was associated with significant toxicity. We have showed using our multiple myeloma xenograft models that more frequent dosing of PLD at lower doses is more effective and better tolerated than higher doses administered less often (13). We have used this approach for treating patients with multiple myeloma (14,15) by combining PLD with bortezomib and i.v.…”
Section: Introductionmentioning
confidence: 99%